China's scientific elite - Cao, Cong, 1959- (RoutledgeCurzon, 2004)
This book is a study of scientists holding membership of the Chinese Academy of Sciences. Cao, among other things, examines the social stratification system of the Chinese science community.
Keywords: Science -- Social aspects -- China.; Scientists -- China.; Elite (Social sciences) -- China.; China -- Intellectual life -- 1976-; Sciences -- Aspect social -- Chine.; Élite (Sciences sociales) -- Chine.; Chine -- Vie intellectuelle -- 1976-; BUSINESS & ECONOMICS -- Knowledge Capital.; Elite (Social sciences); Intellectual life; Science -- Social aspects; Scientists; China; Intellectuelen.; Since 1976